Current concepts in preoperative anemia management in obstetrics. Issue 3 (27th June 2023) - Wiesenack, Christoph; Meybohm, Patrick; Neef, Vanessa; Kranke, Peter
Abstract : Purpose of review: The purpose of this article is to provide an overview of currently recommended treatment approaches for anemia during pregnancy, with a special focus on iron deficiency and iron deficiency anemia (IDA). Recent findings: As consistent patient blood management (PBM) guidelines in obstetrics are still lacking, recommendations regarding the timing of anemia screening and the treatment recommendations for iron deficiency and IDA during pregnancy are still controversial. Based on increasing evidence, early screening for anemia and iron deficiency should be recommended at the beginning of each pregnancy. To reduce maternal and fetal burden, any iron deficiency, even without anemia, should be treated as early as possible during pregnancy. While oral iron supplements administered every other day are the standard treatment in the first trimester, the use of intravenous iron supplements is increasingly suggested from the second trimester onwards. Summary: The treatment of anemia, and more specifically iron deficiency anemia during pregnancy, holds many possibilities for improvement. The fact that the period of risk is known well in advance and thus there is a long optimization phase is per se an ideal prerequisite for the best possible therapy of treatable causes of anemia. Standardization of recommendations and guidelines for screening and treatment of IDA in obstetrics is required for the future. In any case, a multidisciplinary consent is the precondition for a successfully implementation of anemia management in obstetrics to establish an approved algorithm easily enabling detection and treatment of IDA during pregnancy.